Semantics - Lyons, John, 1932-; Cambridge University Press (Cambridge: Cambridge University, 1996)
A general introduction synthesizing work from many disciplines on meaning and communication. Little technical knowledge needed, as all relevant terms and concepts carefully explained.
Vol. 1: -- 1. Introduction: some basic terms and concepts -- 2. Communication and information -- 3. Language as a semiotic system -- 4. Semiotics -- 5. Behaviourist semantics -- 6. Logical semantics -- 7. References, sense and denotation -- 8. Structural semantics I: semantic fields -- 9. Structural semantics II: sense relations.
Includes bibliographical references (volume 1, pages [336]-356) and indexes.
Keywords: Semantics; Semiotics; Grammar, Comparative and general